Simulation of metal stamping for panel front door inner part for new automotive model development - Mesuan, Mohd. Ariffin (2010)
The development of metal stamping part in the automotive industry is become more challenging due to the need of all car makers to reduce the development lead time for new model as well as to reduce the body car weight in order to reduce the fuel consumption. In order to reduce the lead time, forming simulation software is used whereas Tailored Welded Blank (TWB) material is used to reduce the weight, part quantity and overall manufacturing cost. In this study the panel front door inner part is selected by reason of its potential of using TWB material. Foming simulation software is used due to its ability to analyze and to predict the quality of stamping part after the stamping process is done. The software used are CATIA and AUTOFORM. CATIA software is used to create detail radius and also the shape of the study part while AUTOFORM software is used to analyze and to predict the result of panel quality so that if there is any problem occur it can be solve at the early stage. Analysis is then done on the formability, thinning condition and surface quality such as crack and wrinkle to determine the problem at the early stage of new model development. In this part study to counter the crack problem, the dies face and draw bead shape are modified while the crack problem at the inner area is solved by introducing the ‘lance cut’ at15mm from die close condition. The cost merit of using TWB material for panel front door inner is proven.